2002
DOI: 10.1038/nature00910
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon loss with woody plant invasion of grasslands

Abstract: The invasion of woody vegetation into deserts, grasslands and savannas is generally thought to lead to an increase in the amount of carbon stored in those ecosystems. For this reason, shrub and forest expansion (for example, into grasslands) is also suggested to be a substantial, if uncertain, component of the terrestrial carbon sink. Here we investigate woody plant invasion along a precipitation gradient (200 to 1,100 mm yr(-1)) by comparing carbon and nitrogen budgets and soil delta(13)C profiles between six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

38
708
18
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 874 publications
(770 citation statements)
references
References 28 publications
38
708
18
6
Order By: Relevance
“…[4] These Mediterranean ecosystems are commonly heterogeneous savanna-like ecosystems, with contrasting plant functional types (PFTs, e.g., grass, shrubs and trees) competing for the water use [Scholes and Archer, 1997;Ramirez-Sanz et al, 2000;Jackson et al, 2002;Baldocchi et al, 2004;Fernandez et al, 2004;Williams and Albertson, 2004]. Despite the attention these ecosystems are receiving, a general lack of knowledge persists about the relationship between ET and the plant survival strategies for the different PFTs under water stress [Baldocchi et al, 2004;Kurc and Small, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…[4] These Mediterranean ecosystems are commonly heterogeneous savanna-like ecosystems, with contrasting plant functional types (PFTs, e.g., grass, shrubs and trees) competing for the water use [Scholes and Archer, 1997;Ramirez-Sanz et al, 2000;Jackson et al, 2002;Baldocchi et al, 2004;Fernandez et al, 2004;Williams and Albertson, 2004]. Despite the attention these ecosystems are receiving, a general lack of knowledge persists about the relationship between ET and the plant survival strategies for the different PFTs under water stress [Baldocchi et al, 2004;Kurc and Small, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Species compositional shifts caused by woody encroachment into grasslands have important implications for community dynamics and ecosystem properties, such as carbon (C) storage and nitrogen (N) cycling (Post et al 1982;Reich et al 2001b;Jackson et al 2002;McCulley et al 2004;Knapp et al 2008;McKinley and Blair 2008;Barger et al 2011). While regional distributions of woody plants appear to be co-constrained by large-scale differences in precipitation and fire regimes (Staver et al 2011), local success of woody plants in grasslands is strongly associated with a change in disturbance regime that favors woody plants over herbaceous species, such as fire suppression (Van Auken 2000; Roques et al 2001;Silva et al 2001) or increased grazing pressures by cattle (Archer et al 1995;Brown and Archer 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies concerning mechanisms of the SOC sequestration and emission in planted forest have focused on the SOC content and storage change [12,15], and there is no consensus on the changes in SOC pools following afforestation. Studies have reported accumulation [17][18][19], no net change [20][21][22], or loss [12,16,23] of SOC storage after afforestation. The disparity may be due to a number of factors, including sampling depth, regional climate, previous land use, tree species, and stand ages [23][24][25].…”
mentioning
confidence: 99%
“…Studies have reported accumulation [17][18][19], no net change [20][21][22], or loss [12,16,23] of SOC storage after afforestation. The disparity may be due to a number of factors, including sampling depth, regional climate, previous land use, tree species, and stand ages [23][24][25]. SOC turnover time, as a parameter for estimating soil carbon flux, is important for understanding the dynamics of SOC [26][27][28], but little has been done to evaluate the soil carbon pool change based on the SOC turnover times for the soils under planted forests.…”
mentioning
confidence: 99%